How to decrease teenage pregnancy: rural perspectives in Ecuador - Tituaña, Allpa; Herrán, Keren; Galárraga, Omar; Palacios, Iván (Frontiers in Public Health, 2024)
Introduction This study aimed to understand the sociocultural context of teenage pregnancy in an Ecuadorian city with a large indigenous population, to gauge the acceptability of a multifaceted pregnancy prevention program for adolescents, and to elicit perspectives on the optimal program design from adolescents and adult key informants. Methods We ascertained qualitative data via an online, electronic survey administered from August to September 2020. Open- and closed-ended questions elicited perspectives relating to burden of adolescent pregnancies, acceptability of pregnancy prevention programs, and optimal design of future programs. Twenty-four adolescents (13–19 years of age) and 15 adult key informants working in the healthcare, business, and education sectors in Cotacachi completed the survey. Survey responses were analyzed using a structural and in vivo coding, and an inductive approach to consensus-building around key themes. Results Most adolescent survey respondents (75%) believed that teen pregnancy is “fairly common” in Cotacachi, and 41.7% believed differences in teen pregnancy rates are not associated with ethnicity. In comparison, 66.7% of adult survey respondents said teen pregnancy disproportionately occurs among indigenous teenagers. Additionally, 45.8% of adolescent and 80% of adult survey respondents believed that a comprehensive sexual education program would help reduce teenage pregnancy rates by imparting reliable sexual health knowledge. Adult respondents noted that the past programs were unsuccessful in preventing teenage pregnancy because of these programs’ inability to fully engage teenagers’ attention, very short time duration, or inappropriate consideration of cultural context. Discussion In Cotacachi, Ecuador, a sexual health education program is both desired and feasible according to adult and teenager key informants. A successful program must adapt to the cultural context and engage youth participation and attention.